The Genesis of Higher Education Internationalisation - D. А. Smaliakou (Образование и наука, 2019)
Introduction. Nowadays, scientific and educational community underestimates the importance of fundamental research in the field of internationalisation of higher education. Meanwhile, the definition of the philosophical foundations of this phenomenon can shed light on the nature and rules of its development. In this regard, the research of such a fundamental problem as its genesis may affect further affords in the field of its justification, determination of ultimate goals and mechanisms of implementation, as well as interpretation of its ethical, political and spiritual aspects of international academic mobility.The aim of the research was to reveal the real reasons and conditions of internationalisation as a new level of higher education, public and supranational policy.Methodology and research methods. The present research is based on the methodological framework of critical analysis through the retrospective, reflexive, comparative types of analysis, the methods of synthesis, generalisation and systematisation of various scientific points of view.Results and scientific novelty. At present, the philosophical aspects of higher education internationalisation are developed by a small number of scientists, who view its genesis from the perspective of globalisation. Three options are identified: internationalisation as a part of globalisation; internationalisation as a response to the challenges of its development; internationalisation as a phenomenon, which precedes global transformations. In each of these approaches, internationalisation acts as a space of interaction of national actors opposing the unification processes. Meanwhile, the countries-leaders of internationalisation rather act themselves as unifiers, calling into question all theories of the background of the under-discussed phenomenon. The author takes into account the following premises: the destruction of world colonial system and the end of the Cold war, which have actualised the integration agenda in Europe at the end of the 20th century. New international agenda, based on neighborhood strategy and integration, has required not only the development of accustomed horizontal communication, but also the development of vertical communication. The request for time has led to the rise of higher education internationalisation, which replaced the idea of “soft power” and generated national interests, in particular, through channelling of excessive educational resources abroad. When state subjectivity gained the importance of basic value in Europe and in international communication in general, the process of internationalisation was required. Such process increased pan-European competitiveness by combining the efforts of different countries.Practical significance. A clearer understanding of the genesis and the nature of the internationalisation process of higher education will avoid the use of resources at the level of both specific institutions and national institutions and, more importantly, will help to overcome the obstacles to the development of educational systems.